THE EFFECTIVENESS OF ROLE PLAY TECHNIQUE ON MEDICAL STUDENTS’ SPEAKING SKILLS - Sri Wahyuni (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
The purpose of this research was to find out the effectiveness of the role play technique in improving the medical students’ speaking skills. This research employed a quasi experimental research taking the posttest design with two groups. Subjects of this research were the medical students in 2019/2020 year on one private university in West Sumatera. The data were collected through speaking test and measured by using t-test. The result of this research showed that the role play technique had effect in medical students’ speaking ability. It can be seen from the result of t-test (3.68) which had higher than t-table (2.86). Thus, it can be concluded that the role play technique was effective to enhance the medical students’ speaking ability in one of medical universities in West Sumatera.Keywords: Effectiveness, Role Play, Speaking Skills